Analysis of the effect of current ratio (CR), debt to e quity ratio (DER), and total assets turnover (TATO) to return on assets (ROA) (empirical study of food and beverage companies listed on the Indonesian stock exchange period 2018-2021) - Rita Andini; Ahmad Sahri Romadon (Jurnal Info Sains : Informatika dan Sains, 2024)
This study aims to test the Current Ratio (CR), Debt To Equity Ratio (DER), and Total Assets Turnover (TATO) to Return On Assets (ROA). This study used a sample of food and beverage companies listed on the Indonesia Stock Exchange for the 2018-2021 period. This sampling method uses purposive sampling. Based on predetermined criteria, a sample of 35 companies was obtained. This research was conducted with a period of 4 years, bringing the total sample to 140 companies. The type of data used is secondary data taken from the company's financial statements. The analysis technique used in this study was multiple linear regression using the SPSS 25 application program. The results of the study show that the Current Ratio has a non-significant negative impact on Return on Assets, while the Debt to Equity Ratio has a significant negative impact on Return on Assets, and Total Assets Turnover has a significant positive impact on Return on Assets. The coefficient of determination (R2) in this study is 6.40 percent while the remaining 93.6 percent is explained using other variables outside of this study.